In the Lena Delta; a narrative of the search for Lieut.-Commander De Long and his companions, followed by an account of the Greely relief expedition and a proposed method of reaching the North pole - Melville, George W. (George Wallace), 1841-1912.; Phillips, Melville. (Boston : Houghton, Mifflin and Co., 1884)
Mode of access: Internet.